Corrigendum: Usefulness and Potential Pitfalls of Long-Acting Growth Hormone Analogues - Yuen, Kevin C. J.; Miller, Bradley S.; Boguszewski, Cesar L.; Hoffman, Andrew R. (Frontiers in Endocrinology, 2021)
Daily recombinant human GH (rhGH) is currently approved for use in children and adults with GH deficiency (GHD) in many countries with relatively few side-effects. Nevertheless, daily injections can be painful and distressing for some patients, often resulting in non-adherence and reduction of treatment outcomes. This has prompted the development of numerous long-acting GH (LAGH) analogues that allow for decreased injection frequency, ranging from weekly, bi-weekly to monthly. These LAGH analogues are attractive as they may theoretically offer increased patient acceptance, tolerability, and therapeutic flexibility. Conversely, there may also be pitfalls to these LAGH analogues, including an unphysiological GH profile and differing molecular structures that pose potential clinical issues in terms of dose initiation, therapeutic monitoring, incidence and duration of side-effects, and long-term safety. Furthermore, fluctuations of peak and trough serum GH and IGF-I levels and variations in therapeutic efficacy may depend on the technology used to prolong GH action. Previous studies of some LAGH analogues have demonstrated non-inferiority compared to daily rhGH in terms of increased growth velocity and improved body composition in children and adults with GHD, respectively, with no significant unanticipated adverse events. Currently, two LAGH analogues are marketed in Asia, one recently approved in the United States, another previously approved but not marketed in Europe, and several others proceeding through various stages of clinical development. Nevertheless, several practical questions still remain, including possible differences in dose initiation between naïve and switch-over patients, methodology of dose adjustment/s, timing of measuring serum IGF-I levels, safety, durability of efficacy and cost-effectiveness. Long-term surveillance of safety and efficacy of LAGH analogues are needed to answer these important questions.